MANAJEMEN PEMBELAJARAN SECARA ISLAMI - Hasbi Wahy (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
A Teacher has to have a very important role and strategy in the teaching process. No matter how complete the teaching facilities are, how modern the curriculum is and how challenging the media is, the result of the education must be in the hand of the teacher. Because of that a teacher has to have the capa capability and skill on his task. Talking about teaching by using the Islamic strategy he has to be well trained and ready to manage each teaching by integrating Islamic values, and the ability of a teacher in managing the teaching must always be integrated and suitable with the Islamic teaching. The implementation of the Islamic values at a school or â€œMadrasahâ€ are hoped to be able to shape the Islamic characteristic and personality of the student and have a lot of knowledge with wide minded attitude.